2015
DOI: 10.3906/vet-1501-75
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sevoflurane and isoflurane effects on cardiovascular andrespiratory system during spontaneous ventilation in Angora goats

Abstract: IntroductionIsoflurane and sevoflurane are noncombustible halogenated anesthetic agents. In addition to a faster anesthesia induction and shorter recovery time, isoflurane also provides good muscle relaxation. Sevoflurane is more preferable than isoflurane because it has lower irritation of the respiratory tract than isoflurane and it has some advantages such as easy induction and a fast recovery compared to isoflurane (1-3).Propofol, a nonbarbiturate derivative, is a sedative and hypnotic drug that can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In particular, the decrease in the isoflurane group was significant from the 5th min of the anesthesia, compared to the baseline value, whereas it was significant from the 10th min of the anesthesia in the sevoflurane group. These findings were similar to previous studies, where body temperature was reported to decrease in buffalos [6], dogs [9], goats [22] and camels [2] after isoflurane anesthesia, and in dogs [9], cattle [14] and goats [22] after sevoflurane anesthesia. In the current study, regarding body temperature, there were no significant differences between isoflurane and sevoflurane anesthesia.…”
Section: Discussionsupporting
confidence: 82%
“…In particular, the decrease in the isoflurane group was significant from the 5th min of the anesthesia, compared to the baseline value, whereas it was significant from the 10th min of the anesthesia in the sevoflurane group. These findings were similar to previous studies, where body temperature was reported to decrease in buffalos [6], dogs [9], goats [22] and camels [2] after isoflurane anesthesia, and in dogs [9], cattle [14] and goats [22] after sevoflurane anesthesia. In the current study, regarding body temperature, there were no significant differences between isoflurane and sevoflurane anesthesia.…”
Section: Discussionsupporting
confidence: 82%
“…Isoflurane and sevoflurane increase the heart rate in dogs, goats [3,4,12,13], whereas the heart rate remains unchanged in horses and calves [14,15]. Contrary to dog and goat, the rate generally decreases in cat, sheep and lambs [6,16,18].…”
Section: Discussionmentioning
confidence: 99%
“…Isoflurane and sevoflurane cause a dose dependent decrease in blood pressure, cardiac output and systemic vascular resistance in goats, dog, horse and sheep [3][4][5]19]. SABP, DABP and MABP values are decreased in dog, horse, goat [12][13][14]. SABP and DABP values increased under isoflurane and sevoflurane anaesthesia in sheep, but these changes were insignificant between isoflurane and sevoflurane groups [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations